A bio-derived sheet-like porous carbon with thin-layer pore walls for ultrahigh-power supercapacitors. (April 2020) - Shang, Tongxin; Xu, Yue; Li, Pei; Han, Junwei; Wu, Zhitan; Tao, Ying; Yang, Quan-Hong
Abstract: Biomass-derived porous carbon materials have attracted considerable attention due to their abundance, low-cost, and rapid regeneration. Here, we report a sheet-like porous carbon prepared by the carbonization and activation of walnut shells for use in high power supercapacitors (SCs), whose pore walls consist of 1–2 carbon layers. This walnut shell based activated carbon (ACWS) has a high specific surface area (SSA) of up to 3577 m 2 g −1 as well as a much better electrical conductivity (720 S m −1 ) than a typical commercial activated carbon (YP–80F, 93 S m −1 ). As a SC electrode material, the ACWS delivers an ultrahigh capacitance of 330 F g −1 at a current density of 0.1 A g −1 and a high capacitance retention of 81% with the current densities increasing from 0.5 to 100 A g −1 in 6 M KOH, which is far higher than that of YP-80F. This can be attributed to optimum tortuosity for ion transport that is derived from its 2D pore structure. More promising, fully packaged devices based on ACWS achieve ultrahigh power and energy densities of 100 kW kg −1 and 120 Wh kg −1 respectively, in an ionic liquid electrolyte. Overall, this method is easily scalable and simple to prepare a biomass-based carbon with a tunable pore structure for ultrahigh-power SCs. We believe that the result reported here is suggestive of promoting the development of electrode materials for industrial SCs and opening new ways to produce high value-added products from abundant bio-waste. Graphical abstract: The natural waste walnut shells were selected as a precursor to producing a sheet-like activated carbon due to their unique dense texture with a stacked flake structure. The as-obtained porous carbon shows an impressive rate performance in both an aqueous and ionic liquid system, which is attributed to the well-developed porous structure, good conductivity and low tortuosity in the term of ion transport derived from their 2D porous structure. Image 1 Highlights: A sheet-like activated carbon with thin-layer pore walls and good conductivity was produced by dense walnut shells. It can be used as industrial SCs electrode materials due to abundant precursor and easily scalable preparation method. It shows an impressive rate performance with the capacitance of up to 220 F g −1 at 100 A g −1 in an aqueous electrolyte. The corresponding device delivers a high power density of up to 100 kW kg −1 in an ionic liquid electrolyte.